English for Daily Activities: Textbook Developed for Islamic Education Study Program at STAIN Mandailing Natal - Fitriani, Fitriani; Defi, Wahyu Fitrina; Pratami, Fuji (Bulletin of Science Education, 2023)
This research project aims to create teaching materials in the form of textbooks specifically designed for English courses, focusing on "English for Daily Activities" within the PAI study program at STAIN Mandailing Natal. The research methodology employed in this study is research and development, utilizing the ADDIE model (Analysis-Design-Develop-Implement-Evaluate). Data collection involves three main instruments: 1) needs analysis tools, 2) validity assessment tools, and 3) practicality evaluation tools, with the practical stage serving as the project's concluding phase. The outcomes of the research and development process yielded a positive impact on both lecturers and students during the learning process. The validation results indicate high levels of validity, with a total validation percentage of 83.85%, falling within the "very valid" category. Limited trials or practicality testing of the textbooks were conducted by gathering feedback from lecturers and students. The results show strong practicality, with its total percentage of 86.09%, classifying the developed textbook as "very practical" to use by lecturers and students within the Islamic Education Study Program at STAIN Mandailing Natal. Keywords: Textbook, Teaching Materials, Islamic Studies